Methane Oxidation in the Water Column of Xiangxi Bay, Three Gorges Reservoir. Issue 9 (17th September 2019) - Lei, Dan; Liu, Jia; Zhang, Junwei; Lorke, Andreas; Xiao, Shangbin; Wang, Yuchun; Wang, Wei; Li, Ye
Abstract: Four field campaigns are carried out to quantify the methane (CH4 ) oxidation rate in Xiangxi Bay (XXB) of the Three Gorges Reservoir (TGR), China. The water depth of the sampling site varied from 13 to 30 m resulting from the water level fluctuation of the TGR. The CH4 oxidation rates are measured in situ as the decline of dissolved CH4 concentration versus time in incubated, and those rates. The CH4 oxidation rates range from 1.18 × 10 −3 to 3.69 × 10 −3  µmol L −1  h −1, with higher values and stronger variation during summer. A static floating chamber method is used to measure CH4 emitted to the atmosphere resulting in an annual mean flux of 4.79 µmol m −2  h −1 . The CH4 emission rate is significantly negatively correlated with the water level. The results show that a large fraction of CH4 is consumed in the water column with a range of 28.97–55.90 µmol m −2  h −1, accounting for ≈69–98% of the total CH4 input into the water column, and more than 90% is consumed outside the summer, when the water level is lowest. Water depth, which is dominated by water level of the TGR, is a potentially important driver for CH4 oxidation and atmospheric emission in the tributary bay. Abstract : In aquatic systems, methane oxidation plays a fundamental role in reducing methane emissions from aquatic ecosystems to the atmosphere. The methane oxidation in the water column and its emission to the atmosphere are estimated by field campaigns. A large proportion of methane originating from sediments is oxidized in the water column of the reservoir, which is controlled by the water depth.